Retrospective Analysis of a Real-Life Use of Tixagevimab-Cilgavimab plus SARS-CoV-2 Antivirals for Treatment of COVID-19 - Nicolina Capoluongo; Annamaria Mascolo; Francesca Futura Bernardi; Marina Sarno; Valentina Mattera; Giusy di Flumeri; Bruno Pustorino; Micaela Spaterella; Ugo Trama; Annalisa Capuano; Alessandro Perrella (MDPI AG, 2023)
Tixagevimab-cilgavimab is effective for the treatment of early COVID-19 in outpatients with risk factors for progression to severe illness, as well as for primary prevention and post-exposure prophylaxis. We aimed to retrospectively evaluate the hospital stay (expressed in days), prognosis, and negativity rate for COVID-19 in patients after treatment with tixagevimab-cilgavimab. We enrolled 42 patients who were nasal swab-positive for SARS-CoV-2 (antigenic and molecular)-both vaccinated and not vaccinated for COVID-19-hospitalized at the first division of the Cotugno Hospital in Naples who had received a single intramuscular dose of tixagevimab-cilgavimab (300 mg/300 mg). All patient candidates for tixagevimab-cilgavimab had immunocompromised immune systems either due to chronic degenerative disorders (Group A: 27 patients) or oncohematological diseases (Group B: 15 patients). Patients enrolled in group A came under our observation after 10 days of clinical symptoms and 5 days after testing positivite for COVID-19, unlike the other patients enrolled in the study. The mean stay in hospital for the patients in Group A was 21 ± 5 days vs. 25 ± 5 days in Group B. Twenty patients tested negative after a median hospitalization stay of 16 days (IQR: 18-15.25); of them, five (25%) patients belonged to group B. Therefore, patients with active hematological malignancy had a lower negativization rate when treated 10 days after the onset of clinical symptoms and five days after their first COVID-19 positive nasal swab.